Standing at God’s threshold: film viewing as dwelling in Terrence Malick’s The Tree of Life - Pablo Alzola Cerero (Church, Communication and Culture, 2019)
The viewer’s experience of Malick’s cinema can be arguably approached from the notion of dwelling. As Toles points out, the essence of this dwelling derives from the use of the medium’s capacities to reveal the world as something real. In contrast with earlier films, The Tree of Life (2011) opens up the possibility of transcendence by pushing the limits of the world revealed by the film medium: here the world is no more an absolute presence, but the visible sign of a further presence, that of its Creator. The chain of revelations is thus expanded: the filmic dwelling holds the world’s presence and, in turn, this screened world points towards God’s presence. In this vein, the image of Jack O’Brien standing at the enigmatic doorframe in the wilderness might well illustrate the experience of the viewer of The Tree of Life.